Implementasi Pelayanan Kesehatan Reproduksi Remaja dalam UKM PIK-M Garuda Bhakta Berdasarkan Peraturan Pemerintah No 61 Tahun 2014 - Ellatyas Rahmawati Tejo Putri (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
To carry out the constitutional mandate to overcome the very complex problems arising among youth, the Indonesian government, through the BKKBN organization, has launched a program called Generasi Beplan, or GenRe for short, for teenagers. Planning Generation, integrated into the Youth/Student Information and Consulting Center (PIK R/M), aims to provide communication, information, and education services to reproductive health adolescents to create quality adolescents. Many countries have issued regulations on reproductive health services, but implementation is still limited. The author uses a qualitative research method using a descriptive analysis method. The data collected is secondary data in the form of legal regulations related to adolescent reproductive health services. The results of this study indicate that UKM PIK-M Garuda Bhakta has implemented adolescent reproductive health services in the form of KIE provided during peer teacher training. At the same time, KIE (communication, information, and education) is provided formally and informally, as well as activities that empower the younger generation as peer educators. Therefore, implementation of adolescent reproductive health services at Bhakti Wiyata Kediri Institute of Medical Sciences through UKM PIK-M Garuda Bhakta has been carried out in accordance with the constitutional provisions of PP No. 61 of 2014.